2023
DOI: 10.1186/s12941-023-00638-3
|View full text |Cite
|
Sign up to set email alerts
|

“One Health” perspective on prevalence of co-existing extended-spectrum β-lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae: a comprehensive systematic review and meta-analysis

Tsepo Ramatla,
Tshepo Mafokwane,
Kgaugelo Lekota
et al.

Abstract: Background The Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) bacterial isolates that produce extended-spectrum β-lactamases (ESBLs) contribute to global life-threatening infections. This study conducted a systematic review and meta-analysis on the global prevalence of ESBLs in co-existing E. coli and K. pneumoniae isolated from humans, animals and the environment. Methods The systematic review protocol was registered in the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In this study, carbapenemase genes were detected in two (7.6%) P. mirabilis isolates. Since direct transmission of extended‐spectrum cephalosporin‐resistant isolates from animals to humans has been documented, this is a serious concern for veterinary medicine as well as human medicine (Marshall & Levy, 2011; Ramatla et al., 2024).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, carbapenemase genes were detected in two (7.6%) P. mirabilis isolates. Since direct transmission of extended‐spectrum cephalosporin‐resistant isolates from animals to humans has been documented, this is a serious concern for veterinary medicine as well as human medicine (Marshall & Levy, 2011; Ramatla et al., 2024).…”
Section: Discussionmentioning
confidence: 99%
“…Another study did a comprehensive review and meta-analysis to determine the global prevalence of ESBL in co-existing E. coli and K. pneumoniae isolates from humans, animals, and the environment [ 116 ]. A total of 126 studies from Asia ( n = 80), Africa (n = 37), Europe (n = 11), and North America (n = 8), published from 1990 to 2022, were analyzed.…”
Section: One Healthmentioning
confidence: 99%
“…Previous investigation showed that the infections caused by ESBLsproducing E. coli are related to fewer therapeutic options, longer hospital stays, and higher health costs than those caused by non-ESBLs-producing E. coli (Karlowsky et al, 2020). Moreover, a comprehensive systemic review and meta-analysis suggested that the prevalence of ESBLs-producing E. coli has reached 33.0%, 33.5%, and 56.9% for human, animals, and environments, respectively (Ramatla et al, 2023). The intestinal carriage of ESBLs-producing E. coli displayed an almost 8-fold increase from 2.6% in 2003 to 21.1% in 2015 (Bezabih et al, 2021).…”
Section: Introductionmentioning
confidence: 99%